The methodology of Ibn Hajar Al-Asqalani (852 AH) in his book: Fath Al-Bari with the explanation of Sahih Al-Bukhari in the grammatical aspect) - حياة علي حسين الشّمّريّ; أ.د مجيد خير الله راهي الزّامليّ (Journal of College of Education, 2023)
The title of the research: (The methodology of Ibn Hajar al-Asqalani (852 AH) in his book: Fath al-Bari with an explanation of Sahih al-Bukhari in the grammatical aspect). Compilations of explanations of the noble hadith of the Prophet were numerous and varied in various fields, and it was and still is (Fath al-Bari) for the sake of those compilations and the most famous, if not the best, indisputably; For his comprehensive and adequate coverage of the hadiths of Sahih al-Bukhari, and for his explanation of them in an exquisite manner, Anmaz at times in detail and at length in the places that require that, and at other times with simplification and brevity. Its significance, and the commentator researched the grammatical differences of all kinds, absorbing in those differences all opinions on grammatical issues, and then giving his evidence, so he counted the right of a large scientific encyclopedia in which Ibn Hajar deposited various sciences that we can hardly find similar to in explaining another Sunni hadith, where he enriched it as well as  Grammar with valuable investigations in jurisprudence and the sciences of men, revealing the ambiguities of hadith in the text and isnad, as well as useful linguistic investigations, adequate explanation of many Qur’anic verses, their interpretation, the reasons for their revelation, the miracles of the Qur’an in them, and the aspects of its readings with eloquent words of accurate knowledge collected from the mothers of classified books, and great references  . The work of Al-Hafiz in the book was painstaking, as his method of research and dealing with grammatical issues was distinct, and this distinction made him the target of students of knowledge from all sides, and the commentator was also directing some aspects of the syntax according to the meaning included in the text, and sometimes he left the guidance to the reader so that the mind works in it according to For the linguistic flair he enjoys.
Keywords: clarification and guidance of the problem, scholars' disagreement about grammatical issues, interpretation and reasoning